SPEECH ACTS OF GITA’S UTTERANCE ON YOUTUBE - Ummi Hayati (CV. ADIBA ASIHA AMIRA, 2023)
This research deals with an analysis of illocutionary act in Gita’s utterance on YouTube. The objective of this study was to find the types of illocutionary act in Gita’s utterance on YouTube. In collecting data, the writer collected and analyzed through the techniques of discourse analysis. In analysis data, the writer used framework Searle’s (2005) speech acts. The result of the study found out two types of speech acts such as representative and expressive. The representative act was included metaphors, declare, fact, and assertion, meanwhile the expressive act was included pain and dislike.